The Drugs May Be Synthetic but the Consequences are not:Analysis of Synthetic Cannabinoid User Accounts. Issue 4 (2nd April 2020) - Angulski, Kate; Gerber, Jurg
ABSTRACT: Synthetic cannabinoids are the second most used illicit substance among U.S. adolescents. Despite their prevalence and dangers, we know little about the characteristics associated with use. While clinical samples have shed some light on how synthetic cannabinoids differ from marijuana, they have not explored career trajectories of synthetic cannabinoid users. We analyze online forum posts about people's synthetic cannabinoid use to understand more about these novel psychoactive drugs and the drug careers of those who use.